Recent Canadian Negligence Decisions Relating to Prenatal Care: Implications for Physicians’ Screening Practices - Murdoch, Blake (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
This article summarizes several Canadian court decisions from 2015 onward stemming from wrongful birth and wrongful life litigation. Plaintiff success often turns on whether causation is established, on a balance of probabilities, between a physician’s breach of standard of care and the harm to the parents and/or the child later born. Physicians’ failure to offer or order screening or diagnostic tests has been a source of wrongful birth liability, as too can be failure to ensure patient understanding of results. Physicians should ensure that they recommend diagnostic testing when presented with concerning clinical indications in accordance with professional practice guidance. Given non-invasive prenatal screening’s (NIPS) advantages and the threat of wrongful birth liability for failure to discuss this procedure, it is likely to be propelled into an ever more prominent position as a first-choice offering for aneuploidy screening. Appropriately cautious physician behaviour involves discussing and offering NIPS, and also involves ensuring that results are understood. This can reduce physician liability, improve patient reproductive autonomy, and sometimes benefit patient health by preventing or lessening trauma that informed women may opt to mitigate when granted the opportunity.